1991
DOI: 10.1002/j.1556-6676.1991.tb01540.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Role Induction on Trainees' Perceptions of Supervision

Abstract: The effects of a role‐induction procedure on beginning counselor‐trainees' perceptions of supervision were examined using a 10‐minute audiotaped summary of Bernard's (1979) model of supervision. Nineteen trainees were administered the role‐induction procedure at either the 2nd, 5th, or 9th week of the academic term. Two self‐report scales assessed trainees' conceptualization of supervision as well as expectations and attitudes toward the supervisory process. Results indicated that trainees evaluated supervisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
46
0
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 9 publications
1
46
0
1
Order By: Relevance
“…Role induction at the start of training would greatly benefit the supervisee in this process (Bahrick, Russell, & Salmi, 1991;Creaner, 2014). This may be accomplished through clear contracting with the supervisee whereby the roles and responsibilities of the supervisor and supervisee are made explicit at the outset (Watkins & Scaturo, 2013), thus reducing supervisee anxiety (Ellis, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Role induction at the start of training would greatly benefit the supervisee in this process (Bahrick, Russell, & Salmi, 1991;Creaner, 2014). This may be accomplished through clear contracting with the supervisee whereby the roles and responsibilities of the supervisor and supervisee are made explicit at the outset (Watkins & Scaturo, 2013), thus reducing supervisee anxiety (Ellis, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The WAI was adapted to the coach-athlete context inspired by Bahrick et al (1991). Terms such as "therapist" and "client" were in the case of this study changed to "coach" and "athlete," and references to "client problems" were changed to "athlete issues" or "athlete concerns".…”
Section: Working Alliance Inventorymentioning
confidence: 99%
“…Research has indicated that supervisees who report role conflict or ambiguity also tend to report work-related anxiety, general work dissatisfaction, dissatisfaction with supervision (Olk & Friedlander, 1992), a poor supervisory working alliance (Ladany & Friedlander, 1995), and lack of clarity regarding the supervision process (Bahrick, Russell, & Salmi, 1991). Examples of nonadherence to this guideline, which were reported by 9% of the supervisees, typically involved the supervisor never explaining the supervisee's roles and responsibilities or not ensuring that the supervisee is engaged in relevant counseling activities (e.g., "She made me address envelopes and do her filing").…”
Section: Session Boundaries and Respectful Treatmentmentioning
confidence: 99%